Global Libraries impact planning and assessment progress: part 2. Issue 2 (14th June 2019) - Streatfield, David; Abisla, Richard; Al, Umut; Bunescu, Violeta; Dewata, Yulianto; Garroux, Camila; Greeb, Daniela; Maister, Artiom; Paley, Jeremy; Sharma, Shipra; Sharma, Tripti; Soydal, İrem; et al.
Abstract : Purpose: The purpose of this paper is to report on recent performance measurement and impact evaluation progress made in Brazil, India, Indonesia, Moldova, Turkey and Vietnam as part of the last phase of the Global Libraries Initiative. Design/methodology/approach: The country reports are presented as a series of case studies, in some cases supplementing those reported earlier in this journal. Findings: Recent country-specific survey findings are reported and some conclusions are offered. Research limitations/implications: This paper demonstrates how the adoption of a common approach to library service evaluation across several countries can strengthen research practice at country level beyond the Global Libraries Initiative itself. Practical implications: This paper shares Global Libraries IPA learning at country level with people in other countries who may be contemplating public library evaluation at regional, national or local levels or who are interested in performance measurement and impact evaluation. Social implications: The paper shows how focusing on the impact of public library services on users can enhance the understanding of community requirements and inform the development of more effective services to library users and communities. Originality/value: These case studies reflect concentrated impact evaluation and performance measurement work at country level across a range of countries over more than 18 years.